1975
DOI: 10.1002/dev.420080211
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy from rearing conditions affects chicks' behavior in a novel situation

Abstract: Chicks raised in small or large cages were exposed to a relatively large novel situation at 12 or 24 hr of age. At both ages, chicks from small cages had longer latencies to begin moving and lower activity scores. Age itself had no effect. Apparently, chicks learn the characteristics of their home cage shortly after hatching, and discrepancy from the home affects their response to novel situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…This interpretation has been discussed in detail elsewhere (Magladery, Rovee-Collier, & Collier, 1978) and distinguished from a fear analysis of death feigning (e.g., . Notably, the role of familiar contextual cues has been described as a major factor underlying learning and retention by the young of other species (Infurna, Steinert, & Spear, in press;Smith & Spear, 1978), and visual discrepancies from rearing conditions in particular have been found to affect a number of other behaviors of chicks (Bateson, 1964;Brown, 1975;Candland, Nagy, & Conklin, 1963;Salzen, 1962). Finally, this analysis predicts the reversibility of death-feigning durations which results from reversing social/isolate rearing conditions in very young chicks (Gagliardi & Gallup, Note 1).…”
Section: Discussionmentioning
confidence: 96%
“…This interpretation has been discussed in detail elsewhere (Magladery, Rovee-Collier, & Collier, 1978) and distinguished from a fear analysis of death feigning (e.g., . Notably, the role of familiar contextual cues has been described as a major factor underlying learning and retention by the young of other species (Infurna, Steinert, & Spear, in press;Smith & Spear, 1978), and visual discrepancies from rearing conditions in particular have been found to affect a number of other behaviors of chicks (Bateson, 1964;Brown, 1975;Candland, Nagy, & Conklin, 1963;Salzen, 1962). Finally, this analysis predicts the reversibility of death-feigning durations which results from reversing social/isolate rearing conditions in very young chicks (Gagliardi & Gallup, Note 1).…”
Section: Discussionmentioning
confidence: 96%
“…However, it should be noted that these subjects had the opportunity to see their own bodies and perhaps also their own image reflected in their drinking vessel; moreover, they were housed during isolation between wooden partitions of a color more closely resembling the color of wild plumage than that of the albino subjects. Some studies have indeed shown that animals reared in isolation can become familiar with the partitions of their pens (Bateson, 1966;Brown, 1975;Turpin, 1977), and in a later study Gallagher (1978) remarked that his "previous data were probably influenced by a form of self-imprinting due to the absence of a suitable stimulus during the susceptible ontogenetic period" (p. 488).…”
Section: Behavior Of Subjects Isolated Until Maturity-comparison With...mentioning
confidence: 99%
“…Withdrawal responses have been suggested to be elicited by stimuli that contrast with those that have acquired attractive properties by constituting a dominant feature during the prehatching and early posthatching stages (Brown, 1975;Brown & Hamilton, 1977;Dimond, 1968; Fuller, Reprint requests should be sent to Olof 0. Rydkn,…”
mentioning
confidence: 99%
“…Attractive calls elicit motility and/or vocalization while alarm calls elicit immobility and/or cessation of vocalization (reviewed by Impekoven, 1976a and b;Heaton, Miller, & Goodwin, 1978).The ontogenetic development of a selective responsiveness to species-specific attractive calls has been shown to depend on prenatally acquired levels of adaptation and on early postnatal experiences (reviewed by Gottlieb, 1971Gottlieb, , 1976. Withdrawal responses have been suggested to be elicited by stimuli that contrast with those that have acquired attractive properties by constituting a dominant feature during the prehatching and early posthatching stages (Brown, 1975;Brown & Hamilton, 1977;Dimond, 1968; Fuller, Reprint requests should be sent to Olof 0. Rydkn,…”
mentioning
confidence: 99%